Akt3-Mediated Protection Against Inflammatory Demyelinating Disease - DuBois, Juwen C.; Ray, Alex K.; Gruber, Ross C.; Zhang, Yongwei; Aflakpui, Ranee; Macian-Juan, Fernando; Shafit-Zagardo, Bridget (Frontiers in Immunology, 2019)
Akt is a serine/threonine protein kinase that plays a major role in regulating multiple cellular processes. While the isoforms Akt1 and Akt2 are involved in apoptosis and insulin signaling respectively, the role for Akt3 remains uncertain. Akt3 is predominantly expressed in the brain, and total deletion of Akt3 in mice results in a reduction in brain size and neurodegeneration following injury. Previously, we found that Akt3-/- mice have a significantly worse clinical course during myelin-oligodendrocyte glycoprotein (MOG)-induced experimental autoimmune encephalomyelitis (EAE), an animal model in which autoreactive immune cells enter the CNS, resulting in inflammation, demyelination, and axonal injury. Spinal cords of Akt3-/- mice are severely demyelinated and have increased inflammation compared to WT, suggesting a neuroprotective role for Akt3 during EAE. To specifically address the role of Akt3 in neuroinflammation and maintaining neuronal integrity, we used several mouse strains with different manipulations to Akt3. During EAE, Akt3Nmf350 mice (with enhanced Akt3 kinase activity) had lower clinical scores, a lag in disease onset, a delay in the influx of inflammatory cells into the CNS, and less axonal damage compared to WT mice. A significant increased efficiency of differentiation towards FOXP3 expressing iTregs was also observed in Akt3Nmf350 mice relative to WT. Mice with a conditional deletion of Akt3 in CD4+ T-cells had an earlier onset of EAE symptoms, increased inflammation in the spinal cord and brain, and had fewer FOXP3+ cells and FOXP3 mRNA expression. No difference in EAE outcome was observed when Akt3 expression was deleted in neurons (Syn1-CKO). These results indicate that Akt3 signaling in T-cells and not neurons is necessary for maintaining CNS integrity during an inflammatory demyelinating disease.